2019
DOI: 10.2337/dc19-0550
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and HbA1c in Patients With Type 2 Diabetes: Which Sleep Characteristics Matter Most?

Abstract: OBJECTIVE Poor sleep has been identified as a risk factor for poor glycemic control in individuals with type 2 diabetes (T2D). As optimal sleep can be characterized in several ways, we evaluated which sleep characteristics are most strongly associated with glycated hemoglobin A1c (HbA1c). RESEARCH DESIGN AND METHODS A total of 172 patients with T2D completed 7-day wrist-actigraphy and sleep questionnaires. Linear regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 36 publications
5
49
1
Order By: Relevance
“…Using 7-day wrist actigraphy and sleep questionnaires, a previous study has investigated whether sleep characteristics may act in concert on HbA1c in patients with T2D (N=172). 4 In combination, variability in sleep duration, total sleep duration, and subjective sleep quality was most strongly associated with HbA1c (explaining 10.3% of the variance in HbA1c). 4 Extending these findings, in the present study, we observed a positive dose–response association between the number of sleep problems per subject and HbA1c.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Using 7-day wrist actigraphy and sleep questionnaires, a previous study has investigated whether sleep characteristics may act in concert on HbA1c in patients with T2D (N=172). 4 In combination, variability in sleep duration, total sleep duration, and subjective sleep quality was most strongly associated with HbA1c (explaining 10.3% of the variance in HbA1c). 4 Extending these findings, in the present study, we observed a positive dose–response association between the number of sleep problems per subject and HbA1c.…”
Section: Discussionmentioning
confidence: 90%
“… 4 In combination, variability in sleep duration, total sleep duration, and subjective sleep quality was most strongly associated with HbA1c (explaining 10.3% of the variance in HbA1c). 4 Extending these findings, in the present study, we observed a positive dose–response association between the number of sleep problems per subject and HbA1c. However, no conclusions regarding causality can be drawn due to the cross-sectional study design.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Sleep disturbance is common in patients with type 2 diabetes [16] and a previous study reported the high prevalence of sleep dysfunction in patients with type 2 diabetes, and demonstrated that a high proportion (69%) of type 2 diabetics had a Pittsburgh sleep quality index score ≥ 5, suggesting reduced and disturbed sleep [17]. However, there is limited evidence on the association between sleep disturbance and the risk of incident CVD in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent sleep variability may result in poor sleep quality in individuals with T2D [ 29 ]. In addition, various T2D symptoms may explain the variation in sleep parameters including frequent nocturnal urination, hyperglycemia-related food consumption, hypoglycemia symptoms, obesity, pain, and distress [ 30 ].…”
Section: Introductionmentioning
confidence: 99%